2001
DOI: 10.4049/jimmunol.166.5.3334
|View full text |Cite
|
Sign up to set email alerts
|

Gorillas with Spondyloarthropathies Express an MHC Class I Molecule with Only Limited Sequence Similarity to HLA-B27 that Binds Peptides with Arginine at P2

Abstract: The human MHC class I gene, HLA-B27, is a strong risk factor for susceptibility to a group of disorders termed spondyloarthropathies (SpAs). HLA-B27-transgenic rodents develop SpAs, implicating HLA-B27 in the etiology of these disorders. Several nonhuman primates, including gorillas, develop signs of SpAs indistinguishable from clinical signs of humans with SpAs. To determine whether SpAs in gorillas have a similar HLA-B27-related etiology, we analyzed the MHC class I molecules expressed in four affected goril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 60 publications
0
28
1
Order By: Relevance
“…Analysis of B2705 and B27H114D as to tapasin dependence for peptide loading revealed that wild-type B2705 resembles B44D114H, whereas B27H114D behaves like wild-type B4402. In the absence of tapasin, B2705 efficiently binds the reporter peptide, GRIDK PILK, a high-affinity ligand for B2705 (20). A high concentration (12.8 M) of unlabeled peptide was not sufficient to out-compete the reporter peptide binding (Fig.…”
Section: Position 114 Determines the Peptide-loading Characteristics mentioning
confidence: 99%
“…Analysis of B2705 and B27H114D as to tapasin dependence for peptide loading revealed that wild-type B2705 resembles B44D114H, whereas B27H114D behaves like wild-type B4402. In the absence of tapasin, B2705 efficiently binds the reporter peptide, GRIDK PILK, a high-affinity ligand for B2705 (20). A high concentration (12.8 M) of unlabeled peptide was not sufficient to out-compete the reporter peptide binding (Fig.…”
Section: Position 114 Determines the Peptide-loading Characteristics mentioning
confidence: 99%
“…49 Some associations between autoimmune diseases and MHC have also been reported in nonhuman primate populations. 50,51 However, since these diseases have relatively little effect on reproductive success, it is unlikely that autoimmune diseases have much effect on the distribution of MHC alleles in humans or nonhuman primates.…”
Section: Mhc and Diseasementioning
confidence: 99%
“…2 More sophisticated studies of gorilla leukocyte antigens determined that a class one allele identical to HLA B27 does not exist in gorillas. 258 However, molecular reconstruction of a gorilla class one protein, GoGo-B01, showed binding domains similar to HLA B27, and functional studies showed the ability of GoGo-B01 to bind proteins bound by HLA B27. The role of GoGo-B01 in IA in gorillas needs further investigation, as both affected and unaffected gorillas have this allele.…”
Section: Arthritis In Captive Apesmentioning
confidence: 99%